Investor sentiment and herding in Islamic stocks: An exploration of the moderating role of market capitalization - Pranata, Rengga Madya; Jamaludin, Asep; Nandang, Nandang; Wanta, Wanta (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study examines the impact of investor sentiment on herding behavior in the Indonesian Islamic stock market, with market capitalization as a moderating variable.Design/Methodology/Approach: A quantitative approach is used with secondary data from the Indonesian Stock Exchange (IDX) in the period 2022-2023 on 70 Islamic companies. Investor sentiment was measured using the Google Search Volume Index (GSVI), while herding behavior was analyzed using the Lakonishok, Shleifer, and Vishny (LSV) method. Market capitalization is categorized into blue chip, middle chip, and lower chip, and moderated regression analysis (MRA) is applied. The data used meets the criteria of 136 data.Research findings: Investor sentiment significantly influences herding behavior among domestic and foreign investors. Positive sentiment drives stock purchases, while negative sentiment accelerates sell-offs. Market capitalization strengthens the impact of sentiment on herding, especially in small-cap stocks, which are more sensitive to market fluctuations. Theoretical contribution/ Originality: This study highlights the moderating role of market capitalization in sentiment-driven herding, providing new insights into the dynamics of Islamic stock markets.Practitioner/Policy implication: Regulators should monitor sentiment-driven volatility, while investors need to consider market capitalization when making decisions to mitigate risks.Research limitation/Implication: This study is limited to the Indonesian Islamic stock market and uses GSVI as the sole sentiment measure. Future research could explore broader sentiment indicators for deeper insights.